2017
DOI: 10.1038/ng.3843
|View full text |Cite|
|
Sign up to set email alerts
|

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation

Abstract: Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death.1,2 Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups.3–7 To further define the genetic basis of atrial fibrillation, we performed large-scale, multi-racial meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 18,398 individuals with atrial fibrillation and 91,536 referent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
260
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 292 publications
(274 citation statements)
references
References 39 publications
10
260
0
4
Order By: Relevance
“…At a locus centered on a cluster of sodium channel genes, we identified 3 regions that independently associate with AF within SCN10A , SCN5A and a third signal between both genes. At the previously described TBX5 locus, 8 we detected a novel independent signal close to TBX3 . Pairwise linkage disequilibrium (LD) estimates between the independent variants at both loci were extremely low (r 2 <0.03; Supplementary Table 7 ).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…At a locus centered on a cluster of sodium channel genes, we identified 3 regions that independently associate with AF within SCN10A , SCN5A and a third signal between both genes. At the previously described TBX5 locus, 8 we detected a novel independent signal close to TBX3 . Pairwise linkage disequilibrium (LD) estimates between the independent variants at both loci were extremely low (r 2 <0.03; Supplementary Table 7 ).…”
mentioning
confidence: 55%
“…In recent pre-publication results, Nielsen et al, reported 111 loci from 60,620 AF cases and more than 970,000 referents, 15 including more than 18,000 AF cases from our prior report. 8 We therefore performed a preliminary meta-analysis for the top loci in nonoverlapping participants from these two large efforts with a resulting total of over 93,000 AF cases and more than 1 million referents. In aggregate, we identified at least 134 distinct AFassociated loci ( Supplementary Table 16 ).…”
mentioning
confidence: 99%
“…The largest to date was recently led by our group and others in the Atrial Fibrillation Genetics Consortium or AFGen, and included about 18 000 individuals with AF and over 1 00 000 without, in which 23 genomic loci associated with AF were reported 6. The genes closest to the top signal at each locus implicate transcription factors, cardiac expressed ion channels, myocardial or cytoskeletal genes and other pathways in the pathogenesis of AF (figure 1).…”
Section: Genetic Mapping Of Afmentioning
confidence: 99%
“…For example, the SCN10A locus that was shown to be associated with P wave duration in the current study 6 has also been robustly associated with AF. 10,11 Yet, although this framework is attractive, the complex relationship between P wavederived markers and AF complicates the process of relating the identified genetic variants to mechanisms of AF. This is, in part, related to the multifactorial nature of the arrhythmia.…”
Section: See Article By Christophersen Et Almentioning
confidence: 99%
“…Other transcriptomic approaches, such as coexpression analysis as recently implemented by us in a functional follow up study of a locus identified for Brugada syndrome, may also provide functional hypotheses to be tested experimentally. 20 The progress being made in recent years in dissecting genetic factors contributing to AF, both by means of genetic studies in large cohorts of AF 10 and by the intermediate phenotype approach, is remarkable. With their large collaborative study on P wave indices as intermediate phenotypes, Christophersen et al 6 have made another important contribution along a journey that will eventually lead us through the maze of AF.…”
Section: Tadros Et Almentioning
confidence: 99%